An observer design of nonlinear quarter car model for active suspension system by using backstepping controller - Md. Sam, Yahaya (Institute of Electrical and Electronics Engineers, 2009)
This paper presents the use of backstepping controller in order to construct an active suspension for a quarter car model with observer design. The implementation of backstepping controller is presented in non-linear quarter car model for active suspension system. The movement of the rotational motion of arm has been taking into consideration for this system which has been neglected by the linear system. Backstepping control is a recursive control procedure which breaks a design problem for the full system into a sequence of a design problem for lower order systems [1]. The performance of the proposed controller will be compared with the linear quadratic regulator controller to help validate the result.